2018
DOI: 10.1101/261214
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Flexible sensorimotor computations through rapid reconfiguration of cortical dynamics

Abstract: SummarySensorimotor computations can be flexibly adjusted according to internal states and contextual inputs. The mechanisms supporting this flexibility are not understood. Here, we tested the utility of a dynamical system perspective to approach this problem. In a dynamical system whose state is determined by interactions among neurons, computations can be rapidly and flexibly reconfigured by controlling the system‘s inputs and initial conditions. To investigate whether the brain employs such control strategi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
126
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(133 citation statements)
references
References 88 publications
7
126
0
Order By: Relevance
“…This approach was recently used to study how the brain flexibly controls the timing of behavior [48,49]. By applying dimensionality reduction to neuronal activity recorded from medial frontal cortex, Wang et al found that population activity time courses for different time intervals followed a stereotypical path, but traversed that path at different speeds ( Fig.…”
Section: Population Activity Time Coursesmentioning
confidence: 99%
“…This approach was recently used to study how the brain flexibly controls the timing of behavior [48,49]. By applying dimensionality reduction to neuronal activity recorded from medial frontal cortex, Wang et al found that population activity time courses for different time intervals followed a stereotypical path, but traversed that path at different speeds ( Fig.…”
Section: Population Activity Time Coursesmentioning
confidence: 99%
“…One view is that conceptual knowledge relies on neural ensembles that code for relations among stimuli but are invariant to their physical properties [5][6][7][8][9][10][11][12][13] . Recent evidence hints that when sets of stimuli share relational structure across contexts, they are embedded on parallel low-dimensional neural manifolds, so that a linear decoder learned in one context can be readily repurposed for another [14][15][16][17][18] . By aligning neural state spaces between contexts in this way, one can generalise relational knowledge, for example applying a criterion that distinguishes fast and slow animals to discriminate fast and slow vehicles, such as space rockets and bicycles (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…For each pool in the chain, we have a single readout neuron, which receives synaptic input from all neurons of that pool along with a white Gaussian noise input with mean zero and autocorrelation σ readout δ(t − t ) ( Figure 1a). The dynamics of membrane potential and synaptic inputs for the readout neurons are similar to that in (18) and (19) with the appropriate inputs.…”
Section: Trial-to-trial Timing Variability In a Noisy Homogeneoumentioning
confidence: 98%
“…As behavior is controlled by the nervous system, it is natural to look for the source of some of this variability in the variable activity of neural circuits involved in the production of behavior [2,[4][5][6][7]. Indeed, the neural mechanisms underlying behavioral timing have been extensively studied experimentally [2,[8][9][10][11][12], establishing links between temporal variations of behavior and that of neural activity [13][14][15][16][17][18][19][20]. This neural variability could result from multiple sources such as stochastic events at the level of ion channels [21], synapses [22], and neurons [23]; chaotic activity of neural networks [24,25]; and sensory inference errors [5].…”
Section: Introductionmentioning
confidence: 99%